Pengaruh Kompetensi Digital dan Dukungan Organisasi Terhadap Prokratinasti Kerja Aparatur Sipil Negara di Kantor Gubernur Sumatera Barat - Haniva, Azlina; Chairoel, Lucy; Hastini, Lasti Yossi; Fitri, Melly Eka Yan (Indo-MathEdu Intellectuals Journal, 2026)
The study aims to analyze the effects of digital competence and organizational support on work procrastination, both individually and simultaneously. The research employs a quantitative descriptive approach using Likert-scale questionnaires and field observations. The population includes all ASN in the General Bureau of the West Sumatra Governor’s Office, with a sample of 103 respondents. Data analysis was conducted using SmartPLS to test the validity, reliability, and relationships among variables. The results indicate that high digital competence reduces the tendency to procrastinate, as employees are more capable of managing administrative applications and filing systems effectively. Organizational support, including facilities, training, and technical guidance, enhances employee readiness and motivation. Simultaneous analysis confirms that the combination of both factors significantly suppresses procrastination, while deficiencies in either or both increase the risk of delayed task completion. The study implies that enhancing digital competence and optimizing organizational support are effective strategies for reducing procrastination, improving productivity, and strengthening bureaucratic readiness to meet technology-based administrative demands. Digital transformation in bureaucracy depends not only on technology but also on individual capacity and a supportive work environment, making these findings relevant for policy development, human resource management, and bureaucratic improvement strategies.